35. The distribution of melanomacrophage center in liver and kidney of Tilapia fish that infected by Aeromonas hydrophilic - Dian Pratiwi; Dwinna Aliza; Nazarudin Nazarudin; Zuhrawati Zuhrawati; Hamdani Budiman; Razali Daud (Universitas Syiah Kuala, 2019)
This research aims was to determine the number of melanomacrophage center (MMC) in the liver and kidney of tilapia (Oreochromis niloticus) were injected A.hydrophila. This research uses 15 tilapia fish with an average weight of 200-300 g were divided into 5 groups, the control group, and four treatment groups. All treatment groups were injected bacteria A. hydrophila 10-5 CFU dose as much as 0.01 ml intramuscularly. Kidney and liver of tilapia in the control group and K1 were collected on day 1 post-injection, K2 on day 2 post-injection, K3 on day 3 post-injection, K4 on day 4 post-injection, and K5 on day 5 post-injection. MMC Joomla Data were analyzed by ANOVA. Results of the study group K0, K1, K2, K3, K4, and K5 in the liver was 20 ± 18.19 K0, K1 55.67 ± 38.81, 69.67 ± 18.19 K2, K3 80.33 ± 6, 42, 84 ± 6 K4, K5 88.33 ± 4.9. While the results of the kidneys was 32 ± 4.0 K0, K1 57 ± 41.9, 112.3 ± 16.4 K2, K3 113.3 ± 15.3, 96.3 ± 13.5 K4, K5 119.6 ± 30.4. Conclusion The infection of the longer period the higher the number of MMC.